Evaluasi Sistem Pengolah Data Mortalitas Pasien Rawat Inap Berbasis Komputer di RSUD Dr. Moewardi - Devi Pramita Sari; Sudiro Sudiro; Chriswardani Suryawati (Jurnal Manajemen Kesehatan Indonesia, 2017)
The System processors mortality inpatients there is the problem performance computer. Research objectives, evaluate system processors mortality computer based, based on method of Healt Metricks Networck.This research non experiments with the qualitative method. Collection method used observation system processors mortalitas and in-depth interviews. Informants main the program administrators system as many as six informants.Informants triangulation that is supporting management system processors mortality as much as two informants. The result in components resources not all educated personnel information system or medical record, and there never has been training system processors mortality, there has been no written job description, implementers copies duty with the services provided data morbidity, the lack of space and special computer system ocessors mortality, the absence of written regulations. Components indicators there has been no database doctor ,the act of, and cause of death, and certificates death are printed. A component source of the data was not in accordance between the data on mortalitas manual there are in a register in-patient facilities with data on the computer. Components data management of the data analysis is carried out only by system coordinator processors mortality. Components data products are considered to data was incomplete. The spreading and the use of delivery via email still not yet web based and has not integrated.Advice for the hospital management to distribute and should use designed system processors mortality web-based integrated to the external DKK and Dispendukcapil